Anystipalpus, Antennoseius and Vitzthumia: a taxonomic and nomenclatural conundrum of genera (Acari: Mesostigmata: Dermanyssina), with description of four species of Anystipalpus - Lindquist, Evert E.; Moraza, María L. (Zootaxa, 2009)
The genus Anystipalpus Berlese, 1911, of uncertain prior placement in the superfamilies Ascoidea or Dermanyssoidea, is redescribed, based on reexamination of type and other material of the type-species, A. percicola Berlese, and of material representing Anystipalpus livshitsi (Eidelberg) new combination and two new species, A. labiduricola n. sp. and A. kazemii n. sp. Anystipalpus nataliae (Eidelberg) new combination and Anystipalpus ukrainicus (Sklyar) new combination are determined to be junior synonyms of A. percicola Berlese and A. livshitsi (Eidelberg), respectively, new synonymies. The genus is known thus far only from adult females phoretic under the elytra of carabid beetles and the tegmina of labidurid earwigs in Eurasia. The relationships between it and the closely related Antennoseius Berlese, 1916 and Vitzthumia Thor, 1930, are reviewed, and the options for the family level placement of these genera are reconsidered. Attention is given to some gnathosomatic attributes that are commonly overlooked in description of species of these closely related genera. Phoresy and the role of adult female morphs in the life history of these mites, as well as the extraordinary phoretic association of one species with earwigs are discussed.